Implementation of photographic triage in a paediatric dental, orthodontic, and maxillofacial department during COVID‐19. Issue 4 (1st February 2021) - Davies, Anna; Howells, Ryan; Lee, Sharon M. G.; Sweet, Chris J.; Dominguez‐Gonzalez, Susana
Abstract: Background: During the COVID‐19 pandemic, limitations were placed on face‐to‐face encounters in dentistry and oral and maxillofacial surgery (OMFS) in order to promote physical distancing and reduce viral propagation. To facilitate continued assessment of dental, orthodontic, and maxillofacial emergencies, a photographic triage system was initiated at Alder Hey Children's Hospital (AHCH). We will discuss the benefits this system offers at a patient, clinician, departmental, and NHS service level. Aim: To share our experience of photographic triage during the first 3 months of COVID‐19 lockdown, lessons learned, and recommendations. Design: Prospective data collection over 3 months. Results: 220 photographic referrals were received, and swelling (30%) and dental trauma (27%) were the most common presenting complaints. 57% of referrals were not seen, 23% were seen semi‐urgently, and 20% booked for outpatient review. Of those seen, 7 children were seen elsewhere and 44 were seen face‐to‐face at AHCH, with 8 being admitted. Conclusion: Photographic triage reduced physical encounters and proved useful in training junior staff, assessment of new patient referrals, and first on‐call from home. Implementation should be considered throughout dental, orthodontic, and OMFS departments nationwide. In the event of a COVID‐19 resurgence or emergence of a new pandemic, photographic triage could facilitate physical distancing and service provision.